MENINGKATAN KOMPETENSI KEPALA SEKOLAH MELAKSANAKAN SUPERVISI AKADEMIK MELALUI TEKNIK PERCAKAPAN PRIBADI - ., Slamed . (Universitas Tanjungpura, 2017)
The purposes of this study were to know: 1) how were the procedures of conducting private conversation in an effort to improve the competence of the principals in performing academic supervision; 2) whether private conversation improved the competence of the principals in academic supervision. This type of research was the School Action Research by using a method ofdescription. The results concluded: 1) The process of conducting private conversation done by the procedures: making records of observation, analyzing observation, conducting interviews and conducting private conversation; 2) The technique of private conversation increased the competence of the principals, performing the academic supervision. The point was the increase of the average value experienced from the first cycle to the second cycle. The average value of the competency of the principals conducting the academic supervision in SMA Sinar Kasih Sintang increased by 13%, in SMAN. 1 Sepauk 16% and in SMAN. 2 Sintang 16%.